2018
DOI: 10.3390/molecules23040944
|View full text |Cite
|
Sign up to set email alerts
|

CpG Methylation Changes G-Quadruplex Structures Derived from Gene Promoters and Interaction with VEGF and SP1

Abstract: G-quadruplex (G4) is a DNA/RNA conformation that consists of two or more G-tetrads resulting from four-guanine bases connected by Hoogsteen-type hydrogen bonds, which is often found in the telomeres of chromatin, as well as in the promoter regions of genes. The function of G4 in the genomic DNA is being elucidated and some G4-protein interactions have been reported; these are believed to play a role in vital cellular functions. In this study, we focused on CpG methylation, a well-known epigenetic modification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…Maps of DNMT1 chromatin binding sites and endogenous G4s in human K562 leukaemia cells identified using ChIP-seq and G4 ChIP-seq, respectively, revealed that at CpG islands most G4s occur where DNMT1 is bound, leading to a proposal that G4s regulate DNA methylation by sequestering DNMTs [84]. Conversely, DNA methylation can influence G4 topology [85] and may modulate binding by other G4-associated proteins. For instance, CpG methylation at the hTERT gene promoter was suggested to induce G4 formation, resulting in displacement of the CCCTC-binding factor (CTCF) and elevated transcription [86].…”
Section: Natural G4-binding Proteinsmentioning
confidence: 99%
“…Maps of DNMT1 chromatin binding sites and endogenous G4s in human K562 leukaemia cells identified using ChIP-seq and G4 ChIP-seq, respectively, revealed that at CpG islands most G4s occur where DNMT1 is bound, leading to a proposal that G4s regulate DNA methylation by sequestering DNMTs [84]. Conversely, DNA methylation can influence G4 topology [85] and may modulate binding by other G4-associated proteins. For instance, CpG methylation at the hTERT gene promoter was suggested to induce G4 formation, resulting in displacement of the CCCTC-binding factor (CTCF) and elevated transcription [86].…”
Section: Natural G4-binding Proteinsmentioning
confidence: 99%
“…Methylation appears to affect the formation and stability of G4 and thereby modulate the effect of G4-capable sequences on transcription regulation 12,13 . Tsukakoshi and colleagues found that…”
Section: G4 and Methylationmentioning
confidence: 99%
“…Methylation appears to affect the formation and stability of G4 and thereby modulate the effect of G4-capable sequences on transcription regulation 12,13 . Tsukakoshi and colleagues found that the binding of the transcription factor SP1 to the G4-forming DNA sequence in the promoter of VEGF gene can be altered by CpG methylation.…”
Section: G4 and Methylationmentioning
confidence: 99%
“…This may occur in one of the following ways: Similar methylation-related effects may be expected for G4. For example, CpG methylation appears to affect G4 stability and transcription factor binding to VEGF promoter 12 .…”
Section: Hypothesis: the Regulatory Effects Of Dna Methylation On Neumentioning
confidence: 99%